2022
DOI: 10.1016/j.adro.2022.100901
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Modulated Proton Therapy for Bilateral Breast or Chest Wall and Comprehensive Nodal Irradiation for Synchronous Bilateral Breast Cancer: Initial Clinical Experience and Dosimetric Comparison

Abstract: Intensity modulated proton therapy (IMPT) for bilateral breast/chest wall and comprehensive nodal irradiation for synchronous bilateral breast cancer: initial clinical experience and dosimetric comparison, Advances in Radiation Oncology (2022), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
3
4
0
Order By: Relevance
“…Thus, this further advances the case that proton is heart sparing in this setting. Notably, this coronary sparing has been corroborated in other critical reports [21]. Although cardiac sparing may appear to be the most substantive dosimetric benefit with proton therapy compared with photon therapy in treating patients with bilateral breast cancer, we also found that superior dose falloff and beam shaping conferred by protons, owing to the sharp penumbra, Bragg peak, and spot positioning, can reduce the dose to other adjacent organs.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Thus, this further advances the case that proton is heart sparing in this setting. Notably, this coronary sparing has been corroborated in other critical reports [21]. Although cardiac sparing may appear to be the most substantive dosimetric benefit with proton therapy compared with photon therapy in treating patients with bilateral breast cancer, we also found that superior dose falloff and beam shaping conferred by protons, owing to the sharp penumbra, Bragg peak, and spot positioning, can reduce the dose to other adjacent organs.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, this further advances the case that proton is heart sparing in this setting. Notably, this coronary sparing has been corroborated in other critical reports [ 21 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…No patients developed grade 3 or 4 radiation pneumonitis [ 21 ]. Other reports of proton therapy for breast cancer support this finding [ 27 , 28 ].…”
Section: Rationale For Proton Therapysupporting
confidence: 59%